Analysis of the academic opus of professor M.Sc. Anabelle Ulate Quirós - Blanco, Laura Cristina (2025)
This paper compiles and analyzes the academic work of Professor MSc. Anabelle Ulate Quirós from the University of Costa Rica, highlighting her pioneering role in Costa Rican academia. Ulate was the first woman to become a full professor at the School of Economics and the only woman to have held the positions of Director of the Instituto de Investigaciones en Ciencias Económicas (1997–2000) and Observatorio del Desarrollo (2005–2013) until 2025. As of 2023, she remained the only full-time female professor at the School of Economics. Her work, influenced by the economic crisis of the 1980s, focuses on scientific and technological innovation as a driver of economic growth in Costa Rica, proposing an unorthodox approach that emphasizes the role of public institutions in development. Her excellence, ethics, and academic rigor challenged gender barriers in a predominantly male environment, serving as an inspiration for future generations.